EVOLUSI INFAQ DAN PERBANDINGANNYA KETIKA MASIH BERADA PADA ZAMAN RASULULLAH - Nurfitria Dewi; Wangiman Wangiman; Insan Kamil Visiena Findra; Adi Warma; Zainur Huda (Khazanah: Jurnal Sejarah dan Kebudayaan Islam, 2022)
Muslims have several ways of spending their wealth both to meet their personal needs and for the sake of common needs. One example has been described in the form of a berinfaq routine. This infaq is very attached to Muslims because consciously or not they will spend some of their property voluntarily to meet their needs as a trusted brother. However, it is unexpected that this activity began to have several forms that varied with the development of the times. Infaq is an initiative of administrators and local residents to wait from the community and musaffir who pass by to accommodate infaq from them. This happens not only in one place but almost in some mosques located adjacent to the causeway will apply the same thing. In order to reveal the origin and motives of this infaq applies almost all regions in Indonesia, interviews are conducted directly to the mosques concerned. The target mosque interview is around the area in Bukittinggi and the author hopes that this data has represented other areas.